Genetic Variants in the SCN9A Gene are Detected in a Minority of Erythromelalgia Patients - Mari Skystad Kvernebo; Celene Grayson; Ioannis M. Stylianou; Virginia Woloshen; Christopher Radomski; Cato Mørk; Knut Kvernebo (Acta Dermato-Venereologica)
Gain-of-function variants in the voltage-gated sodium channel Nav1.7, encoded by the SCN9A gene, have previously been identified in patients with erythromelalgia, a clinical diagnosis defined by intermittent attacks of painful, hot, swollen, and red skin, predominantly involving the hands and feet. Symptoms are induced or aggravated by warming and relieved by cooling. In primary erythromelalgia there is no known underlying disease. This study investigated the frequency of SCN9A variants in a cohort of primary erythromelalgia patients collected at a single centre, and examined the clinical signs and symptoms associated with identified variants. One hundred patients with possible erythromelalgia were collected prospectively and evaluated by clinical examination. Thirty-five patients fulfilling the clinical criteria of primary erythromelalgia were screened for variants in SCN9A. Five were found to carry likely causal variants, including a variant found in 2 related individuals and a variant not previously described in patients with erythromelalgia. The clinical findings differed significantly between the patients. Overall, in this cohort only 4/34 (11.7%) of unrelated patients had erythromelalgia likely caused by gain-of-function variants in SCN9A. Variants in SCN9A are therefore likely to cause or contribute to primary erythromelalgia in only a small proportion of patients.